2019
DOI: 10.1080/17450128.2019.1576960
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship of social support and family cohesion on ART adherence among HIV-positive adolescents in southern Uganda: baseline findings

Abstract: Several studies in sub-Saharan Africa have linked social support to better ART (antiretroviral therapy) adherence among adults living with HIV. Less is known about the role of social support and family cohesion in ART adherence among children below 18 years. This paper focuses on HIV-infected adolescents as they transition through the vulnerable developmental stage of adolescence to examine the association between family cohesion and social support, and ART adherence in southern Uganda. We utilized baseline da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 34 publications
6
63
1
1
Order By: Relevance
“…Several studies have documented the role of social support, especially from family members in influencing adherence outcomes [30][31][32][33][34][35][36][37][38]. For example, a meta-analysis of studies examining social support and patient adherence to medication showed that ART adherence was 1.74 times higher in patients from cohesive families and 1.53 times lower in patients from families experiencing conflict [30].…”
Section: Social Support and Adherencementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have documented the role of social support, especially from family members in influencing adherence outcomes [30][31][32][33][34][35][36][37][38]. For example, a meta-analysis of studies examining social support and patient adherence to medication showed that ART adherence was 1.74 times higher in patients from cohesive families and 1.53 times lower in patients from families experiencing conflict [30].…”
Section: Social Support and Adherencementioning
confidence: 99%
“…For example, a meta-analysis of studies examining social support and patient adherence to medication showed that ART adherence was 1.74 times higher in patients from cohesive families and 1.53 times lower in patients from families experiencing conflict [30]. In Uganda, family cohesion and social support from caregivers/family were associated with self-reported adherence to ART among HIV-infected adolescents [31]. In another study examining the benefits of family and social relationships for health and mental health of PLWH, family functioning significantly contributed to ART adherence and quality of life [32].…”
Section: Social Support and Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…Testing programmes are often focused on the clinical urgency of testing and on achieving targets such as the UNAIDS 90-90-90 targets, without considering social and relational issues. Notably, there has been much more attention paid to these issues for supporting adherence to treatment in children and adolescents through the provision of social and community based psychosocial support [24,25]. We argue that a similar approach must be adopted for improving uptake of HIV testing, and HIV testing must be regarded as a process rather than a discrete event [26].…”
Section: Discussionmentioning
confidence: 99%
“…I have seen other people die when they are not taking ART. So… I would rather have my child tested so that we know the way forward than to stay in the oblivion age where he/she doesn't know what is going on" [Provider #6,Female,24] Caregivers stated that these factors would impede uptake of HIV testing for children but, importantly, they emphasized that they needed both time and support to work through these concerns and reported that feeling under pressure to quickly move to testing was not conducive to uptake.…”
Section: Limited Paediatric Hiv Literacymentioning
confidence: 99%